Anchored Team Formation Games - Jacob Schlueter; Christian Addington; Judy Goldsmith (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
We propose Anchored Team Formation Games (ATFGs), a new class of hedonic game inspired by tabletop role playing games.We establish the NP-hardness of determining whether Nash stable coalition structures exist, and provide results for three heuristics for this problem. We highlight costs and benefits of each heuristic and provide evidence that all three are capable of finding Nash stable coalition structures, when they exist, much more quickly than a deterministic algorithm.